CONSUMER PROTECTION AGAINST THE CIRCULATION OF BEEF RAISED IN GARBAGE DISPOSAL PLACE - Endri Ristiadi; Tri Andi Mulyandono; Aloysius Andreanto; Ruddy Erieyanto; Arista Candra Irawati (UNTAG Law Review, 2025)
ABSTRACT This article examines consumer protection law regarding the circulation of unfit-for-consumption beef from the Jatibarang Final Disposal Site (TPSA) in Semarang City. The study employs normative and conceptual approaches, analyzing regulations on consumer protection, business responsibility, and law enforcement mechanisms. The findings indicate that although Indonesia has comprehensive regulations for beef distribution, field practices—including cattle grazing at TPSA—pose significant health risks due to heavy metal contamination, microplastics, and pathogens. Consumer protection encompasses the right to safe food, accurate information, and compensation in case of harm. The effectiveness of protection depends on consumer legal awareness, government supervision, and compliance by business actors. The study emphasizes the need for integrated regulation, public education, and consistent law enforcement to ensure food safety. Recommendations are provided for government authorities, law enforcement, academics, and the public to strengthen consumer protection systems and minimize health risks from hazardous food products.